Information Security for BYOD in ABB - Mäenpää, Arto (My University, 2013)
BYOD (Bring Your Own Device) is the future policy in companies that is going to replace the old UWYT (Use What You Are Told) way of thinking. This new policy has a lot of issues both security wisely and policy wisely that needs to get solved before we can fully implement this policy into larger companies. Thanks to large interest in the subject a lot of companies have already come up with solutions to this issue and started to use BYOD policy within their companies. The main target of this Master´s Thesis “Information Security for BYOD in ABB” was to create a working information security system for future BYOD policy use in ABB. For the Thesis we used six different test users with different portable devices and statuses and tried to create a policy that fits well with their job and fulfills the security requirements of ABB. We also discuss a little about cloud computing and how it is good to be included into the final solution for the BYOD security plan.
Keywords: BYOD; Information Security; ABB; Security Planning; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Tietotekniikan koulutusohjelma (DI)|